Klasifikasi Gulma Pada Areal Kebun Praktikum Fakultas Pertanian Universitas Pattimura Ambon - Deyeska Meute; Elia L Madubun; Vilma L Tanasale (Pattimura University Ambon Maluku Indonesia, 2023)
At the location of the former garden in the faculty of agriculture area, various types of weeds were found growing side by side and forming a weed community. The area used to be a former demonstration garden area owned by the faculty of agriculture which was used by students as a practicum area for planting vegetable crops such as kale, mustard greens, spinach and long beans using fertilizer derived from chicken manure and cow dung. After harvesting and left empty, the land grows various types of weeds that coexist in the area. This study aims to describe the various types of weeds in the garden at the faculty of agriculture and find the dominant weed species in the garden at the faculty of agriculture. This study used a vegetation survey method with a 1 m × 1 m kudran. The results showed that 46 types of weeds were found in the former Agriculture faculty garden area with 26 types of dominant weeds and weeds with the highest SDR value in Mimossa pudica weed.